Effect of short-term prehabilitation of older patients with colorectal cancer: A propensity score-matched analysis - Wang, Xiayun; Chen, Ruizhe; Ge, Lili; Gu, Yifan; Zhang, Lin; Wang, Li; Zhuang, Chengle; Wu, Qian (Frontiers in Oncology, 2023)
This study assessed the impact of short-term, hospital-based, supervised multimodal prehabilitation for older patients with colorectal cancer (CRC). A single-center, retrospective study was conducted from October 2020 to December 2021, which included a total of 587 CRC patients who were scheduled to undergo radical resection. A propensity score-matching analysis was performed to reduce selection bias. All patients were treated within a standardized enhanced recovery pathway, and patients in the prehabilitation group received an additional supervised, short-term multimodal preoperative prehabilitation intervention. Short-term outcomes were compared between the two groups. Among the participants, 62 patients were excluded; 95 participants were included in the prehabilitation group and 430 in the non-prehabilitation group. After PSM analysis, 95 pairs of well-matched patients were included in the comparative study. Participants in the prehabilitation group had better preoperative functional capacity (402.78 m vs. 390.09 m, P<0.001), preoperative anxiety status (9% vs. 28%, P<0.001), time to first ambulation[25.0(8.0) hours vs. 28.0(12.4) hours, P=0.008], time to first flatus [39.0(22.0) hours vs. 47.7(34.0) hours, P=0.006], duration of the postoperative length of hospital stay [8.0(3.0) days vs. 10.0(5.0) days, P=0.007), and quality of life in terms of psychological dimensions at 1 month postoperatively [53.0(8.0) vs. 49.0(5.0), P<0.001]. The short-term, hospital-based, supervised multimodal prehabilitation is feasible with a high degree of compliance in older CRC patients, which improves their short-term clinical outcomes.